Canons and Contemporary Danish Literature - Mai, Anne-Marie (Folia Scandinavica Posnaniensia, 2016)
This article deals with recent Danish literature in the light of the discussion about canons occasioned by the publication of the two ministerial canons: Undervisningskanon (Educational Canon, 2004) and Kulturkanon (Cultural Canon, 2006). The article argues that recent Danish literature challenges traditional work categories and the concept of the author on which the two canons are based, and discusses which works and texts in recent Danish literature ought to belong to a future canon.